Analisa Harmonisa Dan Simulasi Filter Pasif Pada Kawat Netral BTS Di Gedung Prodi Teknik Mesin Fakultas Teknik Universitas Kristen Indonesia - Malau, Jekson Supardi; Silalahi, Eva Magdalena; Purba, Robinson (Lektrokom : Jurnal Ilmiah Teknik Elektro, 2023)
This research was conducted on BTS in the Mechanical Engineering Study Program Building, Faculty of Engineering, UKI, Jakarta with the aim of knowing the harmonics on the neutral wire of BTS which includes the level of voltage and current distortion due to the use of non-linear electrical components in BTS. In this study, the standard used as a reference is the IEEE 519-2014 standard. Based on the results of the research conducted, it was found that the Total Harmonic Distortion Current (THDi) at BTS was 224.72% and did not meet the standards. The dominant harmonic currents are 3rd order with 219.02% THDi and 9th order with 47.56% THDi which exceed the IEEE 519-2014 standard limits. And Total Harmonic Distortion Voltage (THDv) is 1.59% and meets the standard. The simulation results of a single tuned LC passive filter can reduce the THDi level of the current flowing in the BTS by 217.66% using Matlab/Simulink software. The current flowing in the neutral wire is based on a measurement of 1.1 amperes with a THDi value of 224.72%, and after being filtered, the THDi drops to 7.06%, but still does not meet the standard. The dominant harmonic currents flowing in the neutral wire are 3rd order with 219.02% THDi and 9th order with 47.56% THDi, which exceed the standard limit and 1.59% overall THDv.